Soft Skills in Modern Education: A New Approach for Effective Educational Communication - Ouldhali, Mohamed (Journal of Humanities & Social Sciences, 2025)
In the face of the rapid transformations the world is experiencing today, academic knowledge alone is no longer sufficient to ensure individuals' success in evolving and dynamic work environments. Soft skills have become essential elements that higher education students must acquire to enhance their abilities in communication, critical thinking, problem-solving, and collaboration with others. These skills not only improve job performance but also contribute to the personal and social growth of students, enabling them to become effective leaders in their communities and professional fields.There is an increasing focus on these skills in higher education institutions, as universities and colleges have recognized that the success of their graduates depends not only on their mastery of academic subjects but also on their ability to interact effectively with others and continuously develop themselves. Hence, integrating soft skills into educational curricula and providing learning environments that encourage students to develop these skills alongside their academic knowledge is of paramount importance.In this context, this article aims to explore the importance of soft skills in higher education and how these skills can help students face future challenges and achieve excellence in their professional and personal lives.
Keywords: soft skills; modern education; Educational programs; communication